MENDALAMI GELAR-GELAR SANTA PERAWAN MARIA BUNDA ALLAH DALAM PENGAKUAN DAN AJARAN FRANSISKUS - Philipus Benitius Metom (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2020)
There is a line of titles of Saint Mary mentioned by Pope Francis in his published encyclicals and apostolic exortations. However, we summarize them into seven new titles, namely, Saint Mary is the daughter of Zion, mother, queen, woman, star, bride, and the spring of happiness for the little people. We consider that the number seven title has opened the minds of the faithful about the joy of believing in the Triune God who saves the world and the significant role of Saint Mary in the success of this exalted work. The recognition of the seven new titles aims to support the understanding of the faith of the Catholic faithful in the Blessed Mary as Mother of God and Virgin. Apart from that, another goal is that the quality of the Church's faith in the virginity of Saint Mary and her mother of God will be strengthened. What kind of quality do you want to affirm? What he wants to affirm is the quality of the Church's faith which is rooted in the past of the Old Testament, which is flourishing and expanding in the present, and which will bear fruit to await eternal happiness in the future (eschatological). Thus, the seven new titles of Saint Mary can reveal the faith of the Church to live at all times.